Arthroscopic labral repair for femoroacetabular impingement: A systematic review. Issue 5 (October 2022) - Migliorini, Filippo; Maffulli, Nicola; Knobe, Matthias; Eschweiler, Jörg; Tingart, Markus; Baroncini, Alice
Abstract: Background: The present systematic review investigated return to sport, patient reported outcome measures (PROMs), complications and subsequent progression to total hip arthroplasty (THA) in patients undergoing arthroscopic labral repair for FAI. Material and methods: Following the PRISMA statement, the literature search was performed in February 2021. The outcomes of interest were: rate of return to sport, modified Harris Hip Score (mHHS), the subscales Activities of Daily Living and Sport-Specific Subscale of the Hip Outcome Score (HOS-ADL and HOS-SSS, respectively). Complications, revision surgeries and progression to total hip arthroplasty were recorded. Results: Data from 210 procedures were retrieved. The mean follow-up was 34.0 (24.0–42.5) months. The mean age of the patients was 32.0 (20.0–47.0) years, while the mean BMI was 20.9 (20.1–21.7) kg/m 2 . 52.8% (111 of 210 patients) were women. At 24-month follow-up, 100% of the patients had returned to sport. At a mean of 34 months follow-up, the mean mHHS increased by 25.5% (P = 0.02), the mean HOS-ADL by 23.0% (P = 0.03), the mean HOS-SSS by 32.8% (P = 0.001). No complications were observed. The rate of revision was 4.3% (9 of 210 procedures). At a mean of 37.9 ± 7.5 months, 1.9% of patients (4/210) underwent THA. Conclusion: Arthroscopic labral refixation for FAI yields reliably positive clinical outcomes, with a low rate of revision and conversion to THA.